AB0930 Towards Objective Measurement Of Spinal Mobility In Axial Spondyloarthritis – Benchmarking An Inertial Measurement Unit System With An Optical Measurement System - Blazek, V.; Loy, N.; Jukic, Elke; Coppers, Birte; Fleischmann, Martha Elisa; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)

POS0494 Fear Of Movement Affects Range Of Motion During Repeated Basmi Exercises Assessed By State-Of-The-Art Motion Capture Techniques - Loy, N.; Blazek, V.; Jukic, Elke; Fleischmann, Martha Elisa; Coppers, Birte; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Quantification of spinal mobility in chronic axial spondyloarthritis (axSpA) is an important component of disease assessment and is currently assessed using the clinical Bath Ankylosing Spondylitis Metrology Index (BASMI). Functional movement-based outcome measures are dependent on a number of secondary factors and, in particular, the impact of fear of movement on BASMI performance in axSpA patients is currently unknown. Objectives: To investigate the association of range of motion (RoM) for repeated BASMI exercises detected by inertial measurement units (IMU) and optical-measurement system (OMS) motion capture with fear of movement by Tampa Scale of Kinesophobia 17 (TSK) [1)] in axSpA patients. Methods: AxSpa patients (Internal Medicine 3, Universitätsklinikum Erlangen) and healthy controls (HC) were asked to fill out the TSK and BASMI was performed and scored for three repetitions for each task by a trained physician. The BASMI tasks were performed a second time on the same day as the clinical assessment using OMS. Fifty-four retro-reflective markers and 16 IMU devices (myoMOTION by Noraxon, Scottsdale, USA) were placed on defined anatomic sites (Figure 1) and marker motion was detected with 11 infrared cameras (Oqus 7+, Qualisys, Göteborg, Sweden). BASMI values for each task were analysed in distance (cm) or degree of rotation. A correlation matrix was used to assess the relationship between TSK score and BASMI task 5 (lateral neck flexion in degrees) values from the OMS and IMU data, using the Pearson product moment correlation. Exact BASMI values in degrees and clinical BASMI value per group are reported as means ± standard deviation (SD). Results: Fifty participants were included in the study (30 axSpa patients (12/16 male/female, age: 41.9 (SD 12.3), C-reactive protein: 5.2 (13.8) mg/l and visual analog scale (VAS) global: 4.1 (SD 2.7)) and 20 HC (9/11 male/female, age: 28.4 (SD 3.7) and VAS global 0.1 (SD 0.29)). Measurements from two patients were excluded due to failed IMU und OMS data post-processing, resulting in 28 patients for this analysis. Correlation results between the exact BASMI-5 scores (degree of rotation) for each of the three repetitions and the TSK scores are presented in Table 1. AxSpA patients showed a positive, but not significant (p>0.05) correlation between OMS and TSK score, and a positive, significant (p<0.05) correlation between IMU and TSK score data. The correlation remained stable over the three repetitions. For the IMU data, significant correlations with the tendency of higher values over each of the three repetitions for both groups were observed. In contrast, the HC values showed a negative correlation for both the OMS and IMU values with the TSK score. An increase over the three repetitions in the negative correlation can be seen for both measurement systems. Conclusion: Our results suggest positive relationship between fear of movement and cervical movement restriction in axSpa patients. In addition, axSpA patients tended to achieve higher levels of mobility on repetition of exercise than at baseline. This influence of fear of movement on functional outcomes is especially visible in the IMU data for the axSpa patients. In contrast, the relationship between fear of movement and cervical movement tends to be negative for HC, suggesting that in healthy subjects fear of movement assessed over the TSK does not impact the objectively measured cervical mobility. Further analysis will include a wider range of BASMI tasks to identify movements that might be particularly prone to impairments due to fear of movemen